ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT PADA BANK PERKREDITAN RAKYAT SYARIAH ( BPRS ) DI BANTEN DAN JAWA BARAT - Hendra Galuh Febrianto; Amalia Indah Fitriana (Universitas Muhammadiyah Tangerang, 2019)
This study aims to empirically examine the effect of significantly the effect of diamond fraud in detecting fraudulent financial statements in BPRS in Banten and West Java that were registered in the Financial Services Authority (OJK) in 2013 - 2017. This research uses secondary data, namely financial statements of 108 companies registered with OJK in 2013 2017. To prove the hypothesis, testing was carried out using eviews 9.0 with panel logistics data. The results of the study show that the BPRS registered with OJK in 2013 - 2017 stated that: Financial Stability, Effective Monitoring, and Capability Variables had no effect on Fraud Financial Statements. While the Rationalization variable affects the Fraud of Financial Statements. McFadden R-squared value is 0.300232, meaning that variations in changes in Fraud fluctuations can be explained by Pressure, Opportunity, Rationalization and Capability by 30%, while the remaining 70% is explained by other variables not examined in this study. Keywords: Financial Report Fraud, Pressure, Opportunity, Rationalization and Capability